In Silico Analysis of Phenolic Compounds from Ceriops decandra Griff. Leaves and Molecular Interaction as Anti Diabetes - Yunita Eka Puspitasari; Mochamad Arega Alfikri; Romasni Sitanggang; Jeny Ernawati Tambunan; Hardoko Hardoko (Science and Technology Indonesia, 2023)
Î±-amylase and Î±-glucosidase in the gastrointestinal tract have an important role in the hydrolysis Î±-1,4 and Î±-1,6 glycosidic chain of starch, respectively. Inhibition of both enzyme activities becomes one of the strategies to control diabetes. However, commercial drugs such as antidiabetics have adverse effects such as gastrointestinal problems. Therefore, exploring functional food, especially from marine natural products as antidiabetic agents, is potential. In particular, Ceriops sp. was reported to contain bioactive compounds with antidiabetic properties, but its mechanism to treat diabetes has not been proved. The potency of phenolic compounds of C. decandra leaves as Î±-amylase and Î±-glucosidase inhibitors were examined in this research by implementing the molecular docking analysis in silico. Three steps of analysis were carried out in this study, including extraction from C. decandra leaves with different polarity solvents, identification of phenolic compounds using LC-HRMS, and molecular docking analysis of phenolic compounds identified from C. decandra leaves. This study revealed that quercetin, rutin, epicatechin, isorhamnetin, caffeic acid, and ferulic acid were identified from C. decandra leaves. According to the drug-likeness and toxicity analysis, the presented compounds in C. decandra leaves had high potential pharmacological properties. Furthermore, molecular interaction analysis exhibited phenolic compounds extracted with ethyl acetate, such as quercetin and epicatechin, and with methanolic extracts, such as quercetin, rutin, epicatechin, and isorhamnetin, were more effective as Î±-amylase and Î±-glucosidase inhibitors than from caffeic acid and ferulic acid. Among the phenolic compounds of C. decandra leaves, rutin and quercetin were predicted to be the potential Î±-glucosidase inhibitors.